Construcción de un sistema automático para el lavado de vehículos con reutilización de agua para la empresa Ecowash. - Pachacama Morales, Andrés Mauricio (2018)
The technical project "CONSTRUCTION OF AN AUTOMATIC SYSTEM FOR WASHING VEHICLES WITH WATER REUSE FOR THE COMPANY ECOWASH", aims to automate the process of washing the company's vehicles to optimize the washing time and waste the least amount of water when implementing a water reuse system. The automation of the process was carried out by means of a PLC and an HMI which allows us a better interaction between the operator and the machine, facilitating the handling of the machine and at the same time speeding up the attention of the customers. Through the PLC it is achieved that the washing process is carried out sequentially, thus making a completely automatic process. A system is designed which allows us to choose between three different types of cars and different types of washing which are selected from the HMI. The calibration of the system is carried out in the field with different types of cars, taking time for the activation of different devices such as motors, electrovalves, pumps and others to be carried out accurately. The water reuse system uses a filtration process through tanks that contain porous material inside which separates the solids present in the water. The reuse system consists of a suction pump that carries the water to the filtration tanks and finally to a storage tank.